Executive Function and Spatial Cognition Mediate Psychosocial Dysfunction in Major Depressive Disorder - Knight, Matthew J.; Baune, Bernhard T. (Frontiers in Psychiatry, 2018)
Background: Cognitive and psychosocial dysfunction are prevalent and disabling features of Major Depressive Disorder (MDD). Emerging evidence suggests that poor cognitive functioning mediates the negative effect of MDD on psychosocial function. However, there is a lack of research examining the domain-specific nature of this relationship. The current study evaluated whether the relationship between MDD and specific psychosocial subdomains (e.g., autonomy, occupational functioning) was mediated by domain-specific cognitive deficits. Methods: Data from 155 participants was obtained from the Cognitive Function and Mood Study (CoFaMS), a cross-sectional analysis of mood, cognition, social cognition, and functioning in individuals with MDD. Cognitive functioning was assessed (Current MDD n= 45, Healthy n= 110), with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), the Colorado Assessment Tests (CATs), and the Psychology Experiment Building Language (PEBL). Psychosocial functioning was clinically evaluated with the Functioning Assessment Short Test (FAST). Results: The results indicated that spatial cognition and executive functioning partially mediated the negative effect of MDD on overall psychosocial functioning, autonomy, and subjective cognition. In contrast, spatial and executive domains showed divergent mediation patterns on interpersonal relationships and leisure time. Conclusions: The findings suggest that executive and spatial cognition play an important role in the pathology of overall psychosocial functioning, and specific functional issues in MDD. Treatments targeting psychosocial recovery in MDD may be improved by emphasising executive and spatial cognitive remediation.